Experimental investigation and testing of impact absorption mechanism for automobiles. (2021) - Jacob, S.; Karikalan, L.; Vijay, S.P.
Abstract: The main objective of our research is to design a Collision Energy Absorption System that overcomes the drawback of all preliminary systems and to design a mechanism which absorbs the impact energy during the one to one collision which will reduce the damages caused to the car by impact energy i.e. collision and to save the lives of the humans who sit inside in a car. During the collision the hydraulic oil which is placed inside the cylinder will be pressurized. Since there is no space for movement of piston, the pressure continues to rise. This rise in pressure will be reduced by breaking of the balls which is placed inside the cylinder with oil. As the balls goes on breaking the piston has the space for movement and so that the pressure decreases. This is way the impact energy produced during collision is being dissipated inside the cylinder. The main goal of our project is inventing a absorption system which will protect the vehicle and the people inside. To design a mechanism this absorbs the impact energy during the one to one collision. To reduce the damages caused to the car by impact energy during the one to one collision. To save the lives of the people who sit inside in a car.